Respuesta :

Answer:

x = -12.071 (3dp)

x = -11.036 (3dp)

Step-by-step explanation:

Step 1: Apply the quadratic formula

(-b±([tex]\sqrt{b²-4ac}[/tex])) / 2a

a = 1 (x²)

b = 10 (10x)

c = 75 (75)

(-10±([tex]\sqrt{10²- 4 x 1 x 75}[/tex])) / 2 x 1

Step 2: Simplify

(-10±([tex]\sqrt{-200}[/tex])) / 2

Step 3: Solve the equation

You must replace ± with first a + then a -.

(-10+([tex]\sqrt{-200}[/tex])) / 2 = -12.071 (3dp) = x

(-10-([tex]\sqrt{-200}[/tex])) / 2 = -11.036 (3dp) = x

Hope this helps!

ACCESS MORE